Meta-Analysis the Effect of Malaria Infection on Anemia in Pregnant Women - Firdausi Nuzula; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2020)
Background: Malaria is an important threat to pregnant women, with an increased risk for both mother and newborn, especially in the first and second pregnancies caused by P. falciparum. Malaria infection in pregnant women can cause anemia in the mother and fetus, as well as babies with low birth weight, this can increase maternal and infant mortality rates. This study aims to analyze the magnitude of the influence of malaria infection in pregnant women on the incidence of anemia based on a number of previous similar studies.Subjects and Method: This was a systematic review and meta-analysis carried out by following the PRISMA flow diagram. The process of searching for articles is carried out through a journal database which includes: Google Scholar, PubMed, and Science Direct by selecting articles published in 2010-2020. Key words used include: